Penerapan Problem-Based Learning dalam Pembelajaran Pemrograman menggunakan Codemonkey untuk Meningkatkan Kemampuan Pemecahan Masalah Siswa Kelas VII: Penelitian - Setyawan Aji Samudra; Syaad Patmanthara; Syeh Umar Anggana; Rasif Nidaan Khofia Ahmadah; Putri Alivia Nabila; Rachman Kurniawan (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The ability to solve problems is a crucial 21st-century skill that should be developed from an early age, including through Informatics lessons at the junior high school level. However, traditional methods of teaching programming are often less effective in stimulating active participation and student understanding. The main focus of this study is to evaluate the effectiveness of implementing a Problem-Based Learning (PBL) strategy combined with the CodeMonkey platform as an effort to develop problem-solving skills among seventh-grade students at SMP Negeri 8 Malang. The method applied in this study is Classroom Action Research (CAR) based on the Kemmis and McTaggart model, carried out over two cycles. Data were obtained through student learning outcome evaluations and analyzed using quantitative methods. Results from the first cycle showed a mastery level of 20% with an average score of 60. After implementing PBL in the second cycle, mastery increased to 83,33% with an average score of 85. The application of problem-based learning proved effective in promoting the improvement of students’ cognitive and social skills through group collaboration, discussions, and mastery of contextual challenges. Therefore, the PBL model combined with interactive media such as CodeMonkey can serve as an innovative and relevant alternative learning strategy to enhance programming skills among junior high school students.